2018
DOI: 10.1007/s00167-018-5082-4
|View full text |Cite
|
Sign up to set email alerts
|

An accelerometer-based portable navigation system improved prosthetic alignment after total knee arthroplasty in 3D measurements

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Ikawa et al [10] conducted a prospective RCT study and reported that 121 unilateral ABN assisted TKA had 287 ml less average blood loss than 120 unilateral conventional TKA (p < 0.05). However, comparable blood loss was proposed by other investigations [23,24]. A recent systematic review and meta-analysis [8] also revealed an insignificant difference in postoperative blood lossrelated indicators between TKA using the ABN and the conventional system.…”
Section: Discussionmentioning
confidence: 60%
“…Ikawa et al [10] conducted a prospective RCT study and reported that 121 unilateral ABN assisted TKA had 287 ml less average blood loss than 120 unilateral conventional TKA (p < 0.05). However, comparable blood loss was proposed by other investigations [23,24]. A recent systematic review and meta-analysis [8] also revealed an insignificant difference in postoperative blood lossrelated indicators between TKA using the ABN and the conventional system.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, some studies in literature reported a reduction of outliers in component position in coronal and sagittal plane using portable accelerometer-based surgical navigation system compared with standard technique for TKA [25e27,29]. In a recent study of 159 patients by Ueyama et al [28], they concluded that using an accelerometer-based portable navigation system (KneeAlign2, OrthAlign Inc, Aliso Viejo, CA) lead to a decrease in the number of outliers of prosthetic alignment in coronal and sagittal planes without any increased complications or operation time. Goh et al compared the alignment accuracy between accelerometerbased navigation and CAS, and they found no differences in lower limb alignment and in position of the femoral component in coronal and sagittal plane between the two groups [35].The purpose of the present study was to investigate whether this system based on accelerometer navigation can be a valuable option to restore neutral alignment with optimal implant position in post-traumatic knee osteoarthritis with femoral or tibial EAD.…”
Section: Discussionmentioning
confidence: 99%
“…Of the six studies investigating whether portable navigation achieved neutral alignment more reliably than conventional methods, two provided Level 1 evidence, one provided Level II evidence and three provided Level III evidence [10,27,28,30,33,35]. Finally, of the six studies investigating whether portable navigation translates to improved clinical results, one provided Level 1 evidence, one provided Level II evidence and three provided Level III evidence [10,28,30,33,35]. Studies reviewed differed with respect to their level of evidence ranging from Level I studies to Level III.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%